Locating the other: a geocriticaldeliberation On tolkien’s middle-earth - Eesha Sajid (Research Parks Publishing LLC, 2021)
This study highlights a salient feature of the setting in J. R. R. Tolkien’s legendarium, the secondary world of Middle-earth: its colonial set-up - a fact, the reader is as much conscious of as the characters are ignorant. Location of Self and Other in the races of Middle-earth, identification of the chief tropes of Self and Other of primary world in those belonging to Middle-earth, and tracing the existence of Othering in the fabric of this initiator of Epic Fantasy are the purposes of this study. This paper has used Geocriticism and its tenet of spatiality as the tool for textual analysis of Middle-earth, as shown and explained chiefly in Lord of the Rings. Events and narratives of The Hobbit and The Silmarillion have also been taken into consideration. This paper brings to light, establishment of Men of West as the Self of Middle-earth by the author, while races of Elves, Hobbits and Orcs serve as the Othered reciprocal to the colonial reality of their world. Several aspects, including comparative geographical and topographical settings, physical and mental delineation of characters belonging to different races, as well as the turns of the plot itself in these works have analyzed in this study. Findings of this paper reveal a perpetuation of colonial and imperialist thought- through the presence and formation of Middle-earth, along with justifications of righteousness of this set up- by the contentment of the characters at their predicament